High-performance binder-free supercapacitors based on electrochemically synthesized 2H-molybdenum disulfide/chlorine-doped graphene oxide (2H-MoS2/Cl-GO) composite electrodes - Hacinecipoglu, Ayse, V; Gencten, Metin (ELSEVIER SCIENCE SA, 2025)
This research investigates the synthesis and characterization of molybdenum disulfide (MoS2) and chlorine-doped graphene oxide (Cl-GO) composites as advanced materials for supercapacitors. Binder-free electrodes were prepared by an electrochemical method at room temperature, marking the pioneering use of 2H-MoS2@ClGO materials in energy storage applications. The synthesis employed cyclic voltammetry (CV) for MoS2 and chronoamperometry (CA) for Cl-GO. Comprehensive characterization, including Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD), elucidated the chemical structures of the materials. Field emission scanning electron microscopy (FESEM) combined with energy dispersive X-ray spectroscopy (EDS) revealed detailed surface morphology and elemental composition. Electrochemical performance evaluation by cyclic voltammetry, electrochemical impedance spectroscopy (EIS) and cyclic charge/discharge tests indicated promising capacitive behavior. The 2H-MoS2@Cl-GO electrode exhibited a specific capacitance of 915.6 mF.cm-2, outperforming the Cl-GO electrode (414.4 mF.cm-2) under similar conditions (0.25 mA.cm-2 in 1.0 M H2SO4 electrolyte). Notably, the electrode retained over 90.2 % of its capacity after 5000 charge-discharge cycles, indicating excellent cycling stability. This study highlights the potential of 2H-MoS2@Cl-GO composites as efficient and durable electrode materials for high performance supercapacitors, providing valuable insights for their practical application in energy storage technologies.
Keywords: Energy storage systems; Supercapacitor; Electrochemical synthesis; Heteroatom doped graphene; Molybdenum disulfide; HYDROTHERMAL SYNTHESIS; MOLYBDENUM SULFIDE; FERRIC-CHLORIDE; ANODE MATERIALS; ENERGY-STORAGE; THIN-FILMS; MOS2; NANOSHEETS; NANOCOMPOSITE; REDUCTION; Chemistry; Electrochemistry